Radio counterparts of gamma-ray sources in the Cygnus region - Benaglia, Paula (2021)
The view of the gamma-ray universe is being continuously expanded by space high-energy (HE) and ground-based very-high-energy (VHE) observatories. Yet, the angular resolution limitation still precludes a straightforward identification of these gamma-ray emitting sources. Radio observations are an effective tool for searching their possible counterparts at lower energies because the same population of relativistic electrons responsible for radio emission can also produce HE/VHE emission via inverse-Compton scattering. The Cygnus region is crowded by many gamma-ray sources, most of them remaining unidentified. In order to find possible counterparts to unidentified gamma-ray sources, we carried out a deep survey of the Cygnus region using the Giant Metrewave Radio Telescope at 610 and 325 MHz. We did a detailed search for counterparts in the error circle of HE/VHE sources. We report 36 radio sources found in the error ellipse of 15 HE sources, and 11 in those of VHE sources. Eight sources have a very steep radio spectral index a < -1.5, these are most likely to be pulsars and will be followed up for a periodicity search. Such a significant number of pulsar candidates within the error circle of HE/ VHE sources prompts a fresh look at the energetics and efficacy of pulsars and pulsar wind nebulae in this context.